### Home > CALC > Chapter 6 > Lesson 6.2.1 > Problem 6-64

6-64.

Let

*f*(*x*)*e*, so that^{x}*f*^{−}^{1}(*x*) = ln*x*. Write an expression that represents each of the expressions below, then simplify. Homework Help ✎*f*(*f*^{−}^{1}*x*))*f*^{−1}(*f*(*x*))*f*(*f*^{−l}(3*x*))*f*^{−l}(*f*(3*x*))

Do you remember the definition of inverse functions?*f*(*x*) and *g*(*x*) are inverses if *f*(*g*(*x*)) = *x*...

Well, *f*(*f*^{ −1}(*x*)) = *e*^{ln}* ^{x}* = ______

Refer to the hint in part (a).

Refer to the hint in part (a).

Let 3*x* = *U*.